Consideração do comportamento não linear das almofadas elastoméricas no tombamento de vigas pré-moldadas - Costa, Lethicia Oliveira (2021)
With advances in concrete technology, precast beams can be dimensioned with very long spans and increasingly slender sections. Consequently, these beams have low lateral bending stiffness, being prone to lateral instability in the assembly phase. In addition, some factors such as initial sweep, initial rotation, camber due to prestressing force and support conditions make the problem of lateral instability more critical. This work aims to evaluate the influence of the non-linearity of contact between beam and pad on the lateral instability of precast beams supported by elastomeric pads, still in the assembly phase. For this, through energy methods, equilibrium equations are defined that simultaneously consider the geometric nonlinearity of the beams and the nonlinearity of contact between beam and support, from which it is possible to determine the limit load and predict beam safety regarding lateral instability. Through the equilibrium equations, the load capacities of a BT-54 beam and a 91.4 m UHPC beam are evaluated. In addition, Monte Carlo simulations are carried out in order to evaluate the influence of parameters such as initial sweep, concrete strength, prestressing force and rotational stiffness of the support. When comparing the solutions proposed in this work with equations that consider the linear stiffness of the spring, there was a reduction in the limit load of up to 84%, due to the consideration of the loss of contact between beam and pad (lift-off), highlighting the importance of considering contact nonlinearity in stability predictions. Regarding the analyzed Ultra High Performance Concrete (UHPC) beam, high sensitivity was found for lateral instability, with a ratio between maximum load and self-weight of up to 1.08, when the technical recommendation is greater than 4. This condition can be improved with the adoption of pads that can absorb tensile stress in the beam-pad interaction, such as pads with adhesion or the use of anchor bolts. Finally, as for parametric analysis, the increase in the initial sweep, the reduction in concrete strength, the increase in prestressing force and the reduction in the rotational stiffness of the support leads to a reduction in the limit load and the increase in the probability of failure, with the concrete strength being a critical parameter for instability, with a probability of failure equal to 0.37% when the strength is equal to 120 MPa, the recommended being equal to or less than 10-4.